Little Cross-Feeding of the Mycorrhizal Networks Shared Between C3-Panicum bisulcatum and C4-Panicum maximum Under Different Temperature Regimes - Řezáčová, Veronika; Zemková, Lenka; Beskid, Olena; Püschel, David; Konvalinková, Tereza; Hujslová, Martina; Slavíková, Renata; Jansa, Jan (Frontiers in Plant Science, 2018)
Common mycorrhizal networks (CMN) formed by arbuscular mycorrhizal fungi (AMF) interconnect plants of the same and/or different species, redistributing nutrients and draining carbon (C) from the different plant partners at different rates. Here we conducted a plant co-existence (intercropping) experiment testing the role of AMF in resource sharing and exploitation by simplified plant communities composed of two congeneric grass species (Panicum spp.) with different photosynthetic metabolism types (C3 or C4). The grasses had spatially separated rooting zones, conjoined through a root-free (but AMF-accessible) zone added with 15N-labeled plant (clover) residues. The plants were grown under two different temperature regimes: high temperature (36/32°C day/night) or ambient temperature (25/21°C day/night) applied over 49 days after an initial period of 26 days at ambient temperature. We made use of the distinct C-isotopic composition of the two plant species sharing the same CMN (composed of a synthetic AMF community of five fungal genera) to estimate if the CMN was or was not fed preferentially under the specific environmental conditions by one or the other plant species. Using the C-isotopic composition of AMF-specific fatty acid (C16:1ω5) in roots and in the potting substrate harboring the extraradical AMF hyphae, we found that the C3-Panicum continued feeding the CMN at both temperatures with a significant and invariable share of C resources. This was surprising because the growth of the C3 plants was more susceptible to high temperature than that of the C4 plants and the C3-Panicum alone suppressed abundance of the AMF (particularly Funneliformis sp.) in its roots due to the elevated temperature. Moreover, elevated temperature induced a shift in competition for nitrogen between the two plant species in favor of the C4-Panicum, as demonstrated by significantly lower 15N yields of the C3-Panicum but higher 15N yields of the C4-Panicum at elevated as compared to ambient temperature. Although the development of CMN (particularly of the dominant Rhizophagus and Funneliformis spp.) was somewhat reduced under high temperature, plant P uptake benefits due to AMF inoculation remained well visible under both temperature regimes, though without imminent impact on plant biomass production that actually decreased due to inoculation with AMF.